2021
DOI: 10.1371/journal.pgen.1009926
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale transgenic RNAi screen identifies transcription factors that modulate myofiber size in Drosophila

Abstract: Myofiber atrophy occurs with aging and in many diseases but the underlying mechanisms are incompletely understood. Here, we have used >1,100 muscle-targeted RNAi interventions to comprehensively assess the function of 447 transcription factors in the developmental growth of body wall skeletal muscles in Drosophila. This screen identifies new regulators of myofiber atrophy and hypertrophy, including the transcription factor Deaf1. Deaf1 RNAi increases myofiber size whereas Deaf1 overexpression induces atroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…Overall, we followed an experimental pipeline (Fig. 1a, b ) similar to the one we recently employed to screen for ubiquitin ligases 60 and transcription factors 66 . Specifically, the UAS/Gal4 system 67 , the skeletal muscle-specific Mef2-Gal4 driver 59 , 68 , and 508 UAS-RNAi transgenic fly stocks were used to knock down 111 evolutionary-conserved myokines that have strong muscle expression (RNA-seq FPKM values ≥4), and assess their role in myofiber growth (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, we followed an experimental pipeline (Fig. 1a, b ) similar to the one we recently employed to screen for ubiquitin ligases 60 and transcription factors 66 . Specifically, the UAS/Gal4 system 67 , the skeletal muscle-specific Mef2-Gal4 driver 59 , 68 , and 508 UAS-RNAi transgenic fly stocks were used to knock down 111 evolutionary-conserved myokines that have strong muscle expression (RNA-seq FPKM values ≥4), and assess their role in myofiber growth (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the screen, we used similar procedures as we recently used 60 , 66 . Specifically, virgin Mef2-Gal4 females (10 flies for each cross) were mated with males (5 flies for each cross) of each RNAi or overexpression stock and transferred to new food tubes every 3 days to avoid overcrowding.…”
Section: Methodsmentioning
confidence: 99%
“…Other circulating factors that may activate proliferation of SC in non-injury states into myofibers include growth hormone, follistatin (a myostatin antagonist), and IGF-1, among others (Forcina et al, 2019;Murach et al, 2021). Additionally, increases in lactate concentrations may act as a signaling molecule for increased proliferation of SCs (Nalbandian et al, 2020), and others have suggested that glycolytic enzymes are necessary for optimal muscle growth, at least in Drosophila models (Graca et al, 2021). However, it is unclear how regulation to either add new nuclei or upregulate existing myonuclear activity is accomplished within muscle fibers (Cramer et al, 2020).…”
Section: Myonuclear Domain and Its Significance To Muscle Functionmentioning
confidence: 99%
“…In vivo RNAi-based genetic screens have proved very successful in identifying novel genes involved in developmental and pathologic processes in a variety of Drosophila somatic tissues when expressed using tissue-specific Gal4 driver lines (Graca et al , 2021; Lesch et al , 2010; Neely et al , 2010; Pletcher et al , 2019; Port et al , 2011; Rotelli et al , 2019; Rylee et al , 2022; Saj et al , 2010; Zeng et al , 2015; Zhou et al , 2019). Hence, we embarked on a candidate genetic screen aimed at identifying factors controlling genome stability.…”
Section: Resultsmentioning
confidence: 99%